Effects of self-regulatory processes on cognitive representation of team-specific tactics in junior male soccer players - Vorraber Lawson, G. A.; Janczura, G. A.; Lex, H. (Movement & Sport Sciences - Science & Motricité, 2020)
The present study aims to demonstrate the relationship between cognitive and behavioral variables that configure expert performance by testing if training in self-regulatory processes would affect the organization of tactics mental representation in soccer. A 2?×?2 mixed design was applied, manipulating the level of training in self-regulatory processes between groups and the moment of evaluation within groups. Participants were 13 under-15 year-old male soccer players from Montevideo, Uruguay, with an average of 9.38?years of competitive experience. The experimental group went through 10 individual weekly sessions of training in self-regulatory processes comprising 11 out of 18 self-regulatory processes presented in Zimerman`s Multiphasic Cycle of Self Regulatory Processes. Greater improvement on the cognitive representation of tactics was observed in the experimental group, which revealed more functionally organized clustering of offensive and defensive team-specific tactical concepts in long-term memory after the training. Results showed significant differences in the organization of tactical knowledge in long-term memory due to the participation in a training program on self-regulatory processes focusing on tactical actions in soccer. This study extended the effects of self-regulatory processes, previously evidenced in specific situations in other sports, to the organization of tactics mental representation in soccer. The effects are related to the facilitation of learning processes caused by the use of self-regulatory processes. The systematic application of learning strategies adapted to tactical situations seemed to enable participants to organize tactical knowledge in long-term memory.